Recent Insight on Regulations of FBXW7 and Its Role in Immunotherapy - Xing, Liangliang; Xu, Leidi; Zhang, Yong; Che, Yinggang; Wang, Min; Shao, Yongxiang; Qiu, Dan; Yu, Honglian; Zhao, Feng; Zhang, Jian (Frontiers in Oncology, 2022)
SCFFBXW7 E3 ubiquitin ligase complex is a crucial enzyme of the UPS which participates in variant activities of cell process, and its component FBXW7 is responsible for recognizing and combining substrates. The expression of FBXW7 is controlled by multiple pathways at different levels. FBXW7 facilitates the maturity and function maintenance of immune cells via functioning as a mediator of ubiquitination-dependent degradation of substrate proteins. FBXW7 deficiency or mutation results in the growth disturbance and dysfunction of immune cell, leads to the resistance against immunotherapy, and participates in multiple illnesses. It is likely that FBXW7 coordinating with its regulators and substrates could offer potential targets to improve the sensitivity and effects of immunotherapy. Here we review the mechanisms of the regulation on FBXW7 and its tumor suppression role in immune filed among various diseases (mostly cancers) to explore novel immune targets and treatments.